2015
DOI: 10.1097/aog.0000000000000909
|View full text |Cite
|
Sign up to set email alerts
|

Pheochromocytoma in a Pregnant Woman With Prior Traumatic Aortic Injury

Abstract: The case underscores the necessity of a meticulous approach to hypertension management and the pivotal role of diligent multidisciplinary collaboration to achieve a safe outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The clinical features of pheochromocytoma crisis vary greatly . As mentioned above, Newell et al defined PMC as catecholamine crisis .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical features of pheochromocytoma crisis vary greatly . As mentioned above, Newell et al defined PMC as catecholamine crisis .…”
Section: Discussionmentioning
confidence: 99%
“…Newell et al emphasized the importance of immediate treatment induction for PMC in order to prevent death. The standard treatment for PMC is same as that of pheochromocytoma, which is surgical resection with alpha‐blocker administration; if surgical resection is unsuccessful, mortality is especially high as a result . Previous reports have indicated that vaginal delivery carries a higher mortality rate (31%) than cesarean section (19%) in cases of pheochromocytoma during pregnancy .…”
Section: Discussionmentioning
confidence: 99%